Impact of the 2019 Novel Coronavirus Disease Pandemic on the Performance of a Cardiovascular Department in a Non-epidemic Center in Beijing, China - Nan, Jing; Zhang, Tong; Tian, Yali; Song, Ke; Li, Qun; Fu, Qiang; Ma, Yan; Jin, Zening (Frontiers in Cardiovascular Medicine, 2021)
Background: Knowledge of the impact of the 2019 novel coronavirus disease (COVID-19) pandemic on the performance of a cardiovascular department in a medical referral hub center from a non-epidemic area of China is limited. Method: The data on the total number of non-emergency medical cares (including the number of out-patient clinic attendances, the number of patients who were hospitalized in non-intensive care wards, and patients who underwent elective cardiac intervention procedures) and emergency medical cares [including the number of emergency department (ED attendances) and chest pain center (CPC attendances), as well as the number of patients who were hospitalized in coronary care unit (CCU) and the number of patients who underwent emergency cardiac intervention procedures] before and during the pandemic (time before the pandemic: 20th January 2019 to 31st March 2019 and time during the pandemic: 20th January 2020 to 31st March 2020) in the Department of Cardiology and Macrovascular Disease, Beijing Tiantan Hospital, Capital Medical University were collected and compared. Results: Both the non-emergency medical and emergency medical cares were affected by the pandemic. The total number of out-patient clinic attendance decreased by 44.8% and the total number of patients who were hospitalized in non-intensive care wards decreased by 56.4%. Pearson correlation analysis showed that the number of out-patient clinic attendance per day was not associated with the number of new confirmed COVID-19 cases and the cumulative number of confirmed COVID-19 patients in Beijing (r = −0.080, p = 0.506 and r = −0.071, p = 0.552, respectively). The total number of patients who underwent non-emergency cardiac intervention procedures decreased during the pandemic, although there were no statistically significant differences except for patent foramen ovale (PFO) occlusion (1.7 ± 2.9 vs. 8.3 ± 2.3, p = 0.035). As for the emergency medical cares, the ED attendances decreased by 22.4%, the total number of CPC attendances increased by 10.3%, and the number of patients who were hospitalized in CCU increased by 8.9%: these differences were not statistically significant. During the pandemic, the proportion of hospitalized patients with ST segment elevation myocardial infarction (STEMI) and non-ST segment elevation myocardial infarction (NSTEMI) significantly increased (19.0 vs. 8.7%, p < 0.001; 28.8 vs. 18.0%, p < 0.001, respectively); also, the number of primary percutaneous coronary intervention (PCI) increased by 10.3%. There was no significant difference between patients before and during the pandemic regarding the age, gender, baseline and discharge medication therapy, as well as length of stay and in-hospital mortality. Conclusions: Our preliminary results demonstrate that both the non-emergency and emergency medical cares were affected by the COVID-19 pandemic even in a referral medical center with low cross-infection risk. The number of the out-patient clinic attendances not associated with the number of confirmed COVID-19 cases could be due to different factors, such as the local government contamination measures. The proportion of hospitalized patients with acute myocardial infarction increased in our center during the pandemic since other hospitals stopped performing primary angioplasty. A hub-and-spoke model could be effective in limiting the collateral damage for patients affected by cardiovascular diseases when the medical system is stressed by disasters, such as COVID-19 pandemic.